Betaine in Inflammation: Mechanistic Aspects and Applications - Zhao, Guangfu; He, Fang; Wu, Chenlu; Li, Pan; Li, Nengzhang; Deng, Jinping; Zhu, Guoqiang; Ren, Wenkai; Peng, Yuanyi (Frontiers in Immunology, 2018)
Betaine is known as trimethylglycine (TMG) and is widely distributed in animals, plants and microorganisms. Betaine is known to function physiologically as an important osmoprotectant and methyl group donor. Accumulating evidence has shown that betaine has anti-inflammatory functions in numerous diseases. Mechanistically, betaine ameliorates sulfur amino acid (SAA) metabolism against oxidative stress, inhibits nuclear factor-κB (NF-κB) activity and NLRP3 inflammasome activation, regulates energy metabolism, and mitigates endoplasmic reticulum (ER) stress and apoptosis. Consequently, betaine has beneficial actions in several human diseases, such as obesity, diabetes, cancer and Alzheimer’s disease.